Edukasi Berbasis Digital untuk Meningkatkan Literasi Keluarga tentang Tuberkulosis Anak di Puskesmas Pauh Kota Padang - Sri Siswati; Aisya Afra Amatullah; Khalisa Innayaturrahmah; Muthia Farhana; Zahwa Rahmadaniputri (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Childhood tuberculosis (TB) remains a major public health concern in Indonesia, where low family awareness and limited treatment support contribute to continued transmission. This study evaluated the effectiveness of a family-centered digital health education intervention in improving literacy regarding childhood TB at the primary care level. A quasi-experimental one-group pre–post test design was conducted among 15 families with confirmed or suspected childhood TB in Pisang Sub-District, Pauh Community Health Center, Padang City. The intervention consisted of door-to-door health education supported by digital media—an animated video and an electronic leaflet, aligned with national childhood TB guidelines. Knowledge outcomes were measured using a validated 20-item questionnaire administered before and after the intervention, and data were analyzed using a paired t-test with a 95% confidence level. Results indicated a substantial improvement in family literacy following the intervention, with mean knowledge scores increasing from 8.70 (SD=1.83) to 14.85 (SD=1.52) (p<0.001). Participants demonstrated better understanding of symptom recognition, household infection prevention, and adherence support roles during treatment. The use of digital media enhanced accessibility and reinforced knowledge retention, confirming its suitability as a family-centered health promotion method. In conclusion, integrating digital health education into home-based interventions effectively strengthens family literacy related to childhood TB and supports national TB control efforts. Broader implementation is recommended through linkage with routine community health services such as posyandu, alongside continuous monitoring of behavioral outcomes to sustain long-term impact.